PipMaker—A Web Server for Aligning Two Genomic DNA Sequences - Schwartz, Scott; Zhang, Zheng; Frazer, Kelly A.; Smit, Arian; Riemer, Cathy; Bouck, John; Gibbs, Richard; Hardison, Ross; Miller, Webb (Genome Research, 2000)
PipMaker (http://bio.cse.psu.edu) is a World-Wide Web site for comparing two long DNA sequences to identify conserved segments and for producing informative, high-resolution displays of the resulting alignments. One display is a percent identity plot (pip), which shows both the position in one sequence and the degree of similarity for each aligning segment between the two sequences in a compact and easily understandable form. Positions along the horizontal axis can be labeled with features such as exons of genes and repetitive elements, and colors can be used to clarify and enhance the display. The web site also provides a plot of the locations of those segments in both species (similar to a dot plot). PipMaker is appropriate for comparing genomic sequences from any two related species, although the types of information that can be inferred (e.g., protein-coding regions andcis-regulatory elements) depend on the level of conservation and the time and divergence rate since the separation of the species. Gene regulatory elements are often detectable as similar, noncoding sequences in species that diverged as much as 100–300 million years ago, such as humans and mice, Caenorhabditis elegans andC. briggsae, or Escherichia coli andSalmonella spp. PipMaker supports analysis of unfinished or “working draft” sequences by permitting one of the two sequences to be in unoriented and unordered contigs.